Ecosystems danh human well-being : (Island Press, 2005)
Our Human Planet summarizes the findings of the four working groups and serves as a reference guide to the four main volumes in the MA series. It presents the key findings of each of the working groups, and meets the needs of policy makers and other professionals. The summary also provides an overview of the framework used by the assessment, and will serve as a guide for assessment, planning, and management for the future.